Metabolic measures 12 months after a randomised controlled trial of treatment of clozapine associated obesity and diabetes with exenatide (CODEX). (May 2020) - Siskind, Dan; Russell, A.; Gamble, C.; Baker, A.; Cosgrove, P.; Burton, L.; Kisely, S.
Abstract: Clozapine is associated with obesity and type 2 diabetes. Glucagon-like-peptide-1 (GLP-1) receptor agonists such as exenatide can counter clozapine-associated GLP-1 dysregulation. Our 24-week randomized, controlled, open-label, pilot trial of once-weekly extended-release subcutaneous exenatide or usual care (CODEX) (n = 28), found exenatide was associated with significantly greater weight loss. We examined whether this effect was maintained at 12-months post-intervention. We followed up CODEX trial participants at 12-months post trial endpoint, collecting information on weight, BMI, waist circumference, blood pressure, fasting glucose, HbA1c, and use of metformin. The primary outcome of interest was change in weight from trial baseline to 12-months post endpoint and trial endpoint to 12-months post endpoint compared between former exenatide and usual care participants. Only HbA1c differed between baseline and 12-months post endpoint between the exenatide and control groups. From endpoint to 12-month follow up there were significantly greater increases among the former exenatide versus former usual care participants for weight, BMI, HbA1c and proportion with >5% weight gain. Stratifying results by whether participants used metformin post trial did not alter proportion with >5% weight gain. Although there were no significant differences in weight and BMI between baseline and 12-month post endpoint, there were significant increases in weight and BMI in the 12 months post endpoint for the former exenatide group. This was irrespective of metformin use and is in keeping with studies of other GLP-1RA agents. Further studies on GLP-1RAs use beyond 24 weeks for people with clozapine associated weight gain are needed.